UNRAVELING MILLENNIAL EMPLOYEE LOYALTY IN THE FOOD AND BEVERAGE INDUSTRY: THE ROLE OF COMPENSATION, CAREER PATH, AND ORGANIZATIONAL CULTURE IN CENTRAL JAVA - Fatwa Zuhanea (ITB AAS Indonesia Surakarta, 2021)
Millennial employee loyalty has emerged as a critical yet elusive organizational challenge, particularly in the food and beverage (F&B) industry where high turnover and generational workforce shifts are endemic. This study examines the influence of compensation, career path, and organizational culture on millennial employee loyalty in food and beverage companies operating in Purbalingga Regency and surrounding areas of Central Java, Indonesia. Anchored in Social Exchange Theory (Blau, 1964), Career Development Theory (Super, 1957; Greenhaus et al., 2010), and Person-Organization Fit Theory (Kristof, 1996), the research employs a quantitative design using Partial Least Squares Structural Equation Modeling (PLS-SEM). A total of 154 millennial employees (born 1981–1996) from 10 F&B companies were surveyed through purposive sampling. Results reveal that compensation (β = 0.318, p < 0.001), career path (β = 0.301, p < 0.001), and organizational culture (β = 0.362, p < 0.001) each significantly and positively influence employee loyalty, jointly explaining 63.1% of variance in loyalty (R² = 0.631). Organizational culture emerged as the strongest predictor, followed by compensation and career path. These findings offer nuanced theoretical and practical contributions to generational HRM in the F&B industry within a developing-country context. Keywords: Millennial Loyalty, Compensation, Career Path, Organizational Culture, Social Exchange Theory